2021
DOI: 10.3390/vaccines9121471
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response to BNT162b2 and ChAdOx1 nCoV-19 Vaccines in Patients with Inflammatory Bowel Disease on Biologic Therapies

Abstract: Introduction: The immunogenicity of SARS-CoV-2 vaccines in patients with inflammatory bowel disease (IBD) on biologic therapies is not well studied. The goal of this study was to measure the serological response to BNT162b2 and ChAdOx1 nCoV-19 vaccines in patients with IBD receiving different biologic therapies. Methods: We performed a multi-center prospective study between 1 August 2021 and 15 September 2021. We measured the seropositivity of SARS-CoV-2 antibodies (SARS-CoV-2 IgG) and neutralizing antibody co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Strong antibody responses were found in the participants who received any COVID-19 vaccine; therefore, patients with IBD are expected to develop immunity from any of the available vaccine strategies, regardless of treatment with immuno-modifying therapies [29]. Similar results were reported in two regional studies that examine the serological response of COVID-19 vaccines in IBD patients receiving biologic therapies [30,31]. This evidence addresses claims that patients on biologic therapies do not mount an immune response to COVID-19 vaccines and can be used to encourage the acceptance of the vaccines.…”
Section: Discussionsupporting
confidence: 53%
“…Strong antibody responses were found in the participants who received any COVID-19 vaccine; therefore, patients with IBD are expected to develop immunity from any of the available vaccine strategies, regardless of treatment with immuno-modifying therapies [29]. Similar results were reported in two regional studies that examine the serological response of COVID-19 vaccines in IBD patients receiving biologic therapies [30,31]. This evidence addresses claims that patients on biologic therapies do not mount an immune response to COVID-19 vaccines and can be used to encourage the acceptance of the vaccines.…”
Section: Discussionsupporting
confidence: 53%
“…However, our study corroborates previous studies that demonstrated significantly reduced antibody levels in immunocompromised IBD patients compared to healthy controls in the 2–12-week period after second vaccination [ 28 , 33 , 34 , 35 , 36 ]. In particular, patients on anti-TNF therapy showed significantly reduced sVNT inhibitory levels and decreased S-IgG levels [ 33 , 34 , 37 , 38 , 39 ]. Shebab et al (2021) and Doherty et al (2022) already demonstrated reduced seroconversion rates in patients on anti-TNF medication [ 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding response of IBD patients to COVID-19 vaccines, a wider breadth of evidence is available, particularly regarding initial response of patients immunized with two doses of the presently available mRNA vaccines (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). Generally, data collected in IBD patients exposed to COVID-19 vaccines resemble those evidenced after SARS-CoV-2 infection.…”
Section: Immune Response Of Patients With Inflammatory Bowel Disease ...mentioning
confidence: 99%